Accounting information systems alignment and SMEs performance: A literature review - Dekeng Setyo Budiarto; Rahmawati M. Agung Prabowo (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
This paper explored the empirical research investigating the relationship between Accounting Information Systems (AIS) alignment and Small and Medium Enterprises (SMEs) performance. Literature shows that AIS alignment is influenced by organizational characteristics, individual characteristics and situational factors which affect SMEs performance. The associate between AIS alignment and firm performance is also discussed in this paper. This paper explores the motivation and contribution of previous researches to identify the gaps for the future studies.
Keywords: L86; M15; M41; 330; Accounting information systems; alignment; small and medium enterprises; firm performance; organizational characteristics; individual characteristics